PENGARAUH MINAT BACA SISWA TERHADAP HASIL BELAJAR PADA SISWA SD NEGERI 01 DESA BUBUSAN JEJAWI - Jannah, Duratul (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2024)
The key to reading is the availability of learning resources. Reading is a complex process. Not only is the reading process complex, but every aspect that occurs during the reading process also works very complexly. By reading we can gain knowledge from various types of knowledge sources, for example books, magazines, novels, newspapers, etc. Interest in reading is only part of the settings that influence the learning outcomes achieved by students. This research aims to determine the influence of interest in reading on student learning outcomes at SD Negeri 01 Bubusan Village. This article aims to determine the factors that influence reading interest and the level of reading interest of students at SD Negeri 01 Bubusan Village in 2024. Data collection techniques consist of direct surveys to the library and documentation. The conclusion of this research is that interest in reading together has a positive impact in growing and increasing interest in reading in children, because interest in reading can increase children's interest and enthusiasm for learning.